1992
DOI: 10.1111/j.1600-0897.1992.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant Compatibility Does Not Exist at the HLA‐DQB Gene Locus in Couples With Unexplained Recurrent Abortions

Abstract: The polymerase chain reaction-restricted fragment length polymorphism (PCR-RFLP) method was used for both examining compatibility at the HLA-DQB1 gene locus and determining HLA-DQ antigen polymorphism in spouses of unexplained recurrent abortions. Genomic DNA samples were prepared from peripheral mononuclear cells from patient and control couples. Two hundred and thirty base pair fragments of the second exon of the HLA-DQB genes were selectively amplified. Amplified DNAs were digested with the restriction endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A series of PUBMED searches were performed in order to identify all relevant studies within the period (1975–2004) that contain MESH terms, such as ‘major histocompatibility complex’, ‘human leucocyte antigen’ and ‘recurrent spontaneous abortion’ and cross‐referenced studies were obtained. A total of 42 studies were identified (17–20, 31–68). Of those, two were later excluded (38, 48), because their main objective was different from testing an effect of HLA on RSA.…”
Section: Methodsmentioning
confidence: 99%
“…A series of PUBMED searches were performed in order to identify all relevant studies within the period (1975–2004) that contain MESH terms, such as ‘major histocompatibility complex’, ‘human leucocyte antigen’ and ‘recurrent spontaneous abortion’ and cross‐referenced studies were obtained. A total of 42 studies were identified (17–20, 31–68). Of those, two were later excluded (38, 48), because their main objective was different from testing an effect of HLA on RSA.…”
Section: Methodsmentioning
confidence: 99%
“…HLA-DQA1*0505), to predispose to abortion when shared between partners (2)(3)(4). The above suggestions have not been widely accepted, given the controversial results provided by different studies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, there have been reports concerning the frequency and sharing of HLA antigens in couples who experienced recurrent spontaneous abortions. Recent investigations, however, demonstrated that the incidence of shared HLA antigens was not significantly higher in couples with unexplained recurrent abortions [4,5,21,27,33]. Recent investigations, however, demonstrated that the incidence of shared HLA antigens was not significantly higher in couples with unexplained recurrent abortions [4,5,21,27,33].…”
Section: Discussionmentioning
confidence: 96%